EFFECT OF VARIOUS PULLING SPEEDS ON THE MECHANICAL PROPERTIES OF VARIOUS FIBER MIXTURE COMBINATIONS OF POLYAMIDE 6 AND 6.6 MATERIALS - Gönenli, Can; Yeni, Emine (MATTER: International Journal of Science and Technology, 2018)
Nowadays, thermoplastic composites have increasingly wide application areas due to their high stiffness and impact strength properties, superior fracture toughness, long duration of raw material shelf life and ease of production processes. Besides, they provide safer work environment. In this study, it has been examined that how the pulling speeds effects mechanical properties of thermoplastic composites. Non-reinforced, 15 percent reinforced and 30 percent reinforced polyamide 6 and polyamide 6.6 samples are produced with using plastic injection molding method and they are subjected to tensile testing at five different pulling speeds using the Tensile Testing Device. The results obtained from testing and those gathered from the plastics manufacturer company are compared with data obtained from the literature to check mechanical properties of thermoplastic composites which have been used in pulling speed test. It is observed that the experimental results were highly consistent with those in literature. According to these results, the positive effect of higher pulling speeds is observed. In this way, the different types of unreinforced and fiber glass reinforced polyamide 6 / polyamide 6.6 samples behavior under different pulling speeds have been determined. The results are in similar behavior with all types of polyamides. In order to gain an understanding of the effect of the overall testing procedure for all speeds, stress–strain graphics are constructed.